Allies of a kind : - Thorne, Christopher (Oxford University Press, 1978)
This book is in many respects a sequel to my study of the West and the Far Eastern crisis of 1931 to 1933, the Limits of Foreign Policy, although it can be read quite independently of that work. It marks a further step, in other words, in what has so far been a nine-year search for an understanding of Western policies, actions and interactions in the Far East following the Japanese attack in Manchuria.